Welfare-Based Altruism - Yves Breitmoser; Pauline Vorjohann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
Why do people give when asked, but prefer not to be asked, and even take when possible? We show that standard behavioral axioms including separability, narrow bracketing, and scaling invariance predict these seemingly inconsistent observations. Specifically, these axioms imply that interdependence of preferences (ältruism\") results from concerns for the welfare of others, as opposed to their mere payoffs, where individual welfares are captured by the reference-dependent value functions known from prospect theory. The resulting preferences are non-convex, which captures giving, sorting, and taking directly. Re-analyzing choices of 981 subjects in 83 treatments covering many variants of dictator games, we find that individual reference points are distributed consistently across studies, allowing us to classify subjects as either non-givers, altruistic givers, or social pressure givers and use welfare-based altruism to reliably predict giving, sorting, and taking across experiments.
Keywords: C91; D64; D03; 330; social preferences; axiomatic foundation; robustness; giving; charitable donations